Poetique et psychologic de I’exil dans septieme printemps de Ramonu Sanusi (2012)
In several postcolonial works of contemporary African writers, we observe that the legacy of the colonization is the inferiority complex of the former (ancient) colonized which believes that the acculturation in the western values and the migration to the West are the) keys to the economic, political and cultural safety (salute). In certain Works, the life in the West ends in a psychological shock of the exile because of the clash of the cultures and the climates. Ramonu Sanusi, a Nigerian bilingual writer produced by the interbreeding between Africa and the West, deals with the problem of the exile of the Africans in the western countries through a collection of poems entitled “Seventh spring”. Because our work discusses the personality of the poet in a post-independence context, we are going to use a psychological approach based on the postcolonial theory to position the poetic work of Sanusi in the postcolonial context of the bilingual Nigerian writers. The analysis of the theme of the exile in the poems of Sanusi will allow us to place the concerns of the poet in the problem of the exile through its causes and consequences, to see if the author is a simple observer or a stakeholder in the cultural context of his story. The analysis by archetypes according to the psychoanalysis of Jung will reveal us how the exile which begins as a quest ends in an initiation. From the illusory exile to the disappointment of the exile, the poet discovers that the Africans of the Diaspora have to return to Africa to end the dictatorship of the leaders and that Africa needs the competence of all the exiles to liberate her from the yoke of diseases and of all the troubles brought about by the economic underdevelopment